Antarctic and New Zealand Byblisoides (Amphipoda: Ampeliscidae) with a key to the world species - Peart, Rachael A. (Zootaxa, 2018)
The family Ampeliscidae is a species diverse family ranging from shallow waters to over 4000 m depth. Within this family, however, one genus, Byblisoides has few species and is generally found in deep water. The conservative morphology of other species of Byblisoides is also evident in the new species described here. This study extends the known species composition of the genus from seven species to nine. A key to world species is updated.